Colonial Destruction of Extractive and Manufacturing Industries, and the Spirit of Trade and Commerce in Southern Kaduna-Nigeria, 1900-1960 - Mallam, Ibrahim (NIU Journal of Humanities; Vol 8 No 4 (2023): NIU Journal of Humanities, Vol. 8 No. 4, December 2023, 2023)
Southern Kaduna refers to all the non-Hausa-Fulani autochthonous language groups in Kaduna State of Nigeria. They do not form a geo-political entity, but a social and geo-cultural one. In spatial terms, the region covers the geo-linguistic and cultural entity of that was commonly referred to as Southern Zaria or Southern Division or “Pagan Division” of Zaria Province, with parts of former Bauchi, Niger, Nasarawa and Plateau Provinces. Southern Kaduna is not a geo-political expression; but the culture-complex sub-region, which together with Jos Plateau and the Federal Capital Territory Abuja, form the heartland of Nigeria. Southern Kaduna is situated within the central high plains of Central Nigeria and is located between Hausa land and the Niger/Benue Valley. It is located between Longitude 7 0 45' 20"N to 8 0 30' 15"N and Latitude 9 0 01' 34"E to 10 0 57' 30"E.